Effect of dexmedetomidine on liver transplantation: a meta-analysis - Jia, Degong; Guo, Shanshan; Wu, Xinyi; Zhao, Minjie; Luo, Jiefu; Cheng, Mingxiang; Qin, Yajun (Frontiers in Pharmacology, 2023)
Background: Dexmedetomidine (DEX), an adjuvant anesthetic, may improve the clinical outcomes of liver transplantation (LT). Methods: We summarized the relevant clinical trials of DEX in LT. As of 30 January 2023, we searched The Cochrane Library, MEDLINE, EMBASE, and ClinicalTrial. gov and WHO ICTRP. The main outcomes were postoperative liver function and renal function. The random effect model or fixed effect model was used to summarize the outcome across centers based on the differences in heterogeneity. Results: The meta-analysis included nine studies in total. Compared with the control, DEX reduced the warm ischemia time (MD -4.39; 95% CI-6.74–2.05), improved postoperative liver function (peak aspartate transferase: MD -75.77, 95% CI -112.81–38.73; peak alanine transferase: MD -133.51, 95% CI-235.57–31.45) and renal function (peak creatinine: MD -8.35, 95% CI-14.89–1.80), and reduced the occurrence of moderate-to-extreme liver ischemia‒reperfusion injury (OR 0.28, 95% CI 0.14-0.60). Finally, the hospital stay of patients was decreased (MD -2.28, 95% CI-4.00–0.56). Subgroup analysis showed that in living donors, prospective studies and adult recipients, DEX may have better efficacy. Conclusions: DEX can improve short-term clinical outcomes and shorten the hospital stay of patients. However, the long-term efficacy of DEX and its interfering factors deserves further study.